2009
DOI: 10.1016/j.cplett.2009.05.064
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced fluorescence emission of Me-ADOTA+ by self-assembled silver nanoparticles on a gold film

Abstract: We report a multi-fold enhancement of the fluorescence of methyl-azadioxatriangulenium chloride (Me-ADOTA•Cl) in PVA deposited on a 50 nm thick gold mirror carrying an evaporation induced self-assembly of colloidal silver nanoparticles (Ag-SACs). The average measured increase in fluorescence emission of about 50-fold is accompanied by hot spots with a local enhancement in brigthness close to 200. The long lifetime of the dye allows for the first direct determination of the correlation between the enhancement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 29 publications
1
44
0
Order By: Relevance
“…Recently, a fluorescence enhancement of ~200-fold on colloidal silver nanoparticles was reported; however, only for selected “hot spots” on a gold mirror. 12 It is important to note that AF647-SA is one of the brightest organic fluorophores with a quantum efficiency better than 0.30 and high extinction coefficient of 239 000 M −1 cm −1 , which is spectrally equivalent to widely used Cy 5 fluorophore for biomolecule labeling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a fluorescence enhancement of ~200-fold on colloidal silver nanoparticles was reported; however, only for selected “hot spots” on a gold mirror. 12 It is important to note that AF647-SA is one of the brightest organic fluorophores with a quantum efficiency better than 0.30 and high extinction coefficient of 239 000 M −1 cm −1 , which is spectrally equivalent to widely used Cy 5 fluorophore for biomolecule labeling.…”
Section: Resultsmentioning
confidence: 99%
“…5,12,31 Accordingly, the lifetime measurements provide valuable information about the mechanism of the enhancement. For example, if the intensity is enhanced but the lifetime is not changed, this means that the mechanism of intensity enhancement is due to an enhanced excitation intensity or an increase in the fluorophore concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sørensen et al found about similar enhancement in hot spots where fractals were deposited on gold mirror and dye was deposited directly on the fractals [25]. Thus, different configuration of PP did not affect the fluorescence enhancements.…”
Section: Discussionmentioning
confidence: 93%
“…The azaoxa-triangulenium class of dyes, 1214 in the following represented by azadioxatriangulenium (ADOTA + , Figure 1), are bright organic dyes with a long fluorescence lifetime (≈25 ns) and emission in the red. 15, 16 The fluorescence lifetimes are comparable to those of dansyl and pyrene. However, the emission at 550–600 nm results in much reduced interference from protein auto-fluorescence and Rayleigh scattering.…”
Section: Introductionmentioning
confidence: 86%